Correlation of Vitamin D and Bone Mineral Density in Postmenopausal Women in 3 Different Regions of Turkey - Original Investigation - Merih Sarıdoğan; Ülkü Akarırmak; Nurten Eskiyurt; Şansın Tüzün (Galenos Yayinevi, 2010)
Aim: To find the correlation with regard to various age groups between bone mineral density (BMD) measured in spine and hip areas and Vitamin D level in 3 different cities. Material and Methods: The 3 cities (Marmara, Egean, South Turkey) were located in different geographical regions. BMD was measured with DXA in spine (L1-4) and hip (femur neck and femur total) areas by Hologic QDR4500. Serum Vitamin D and calcium levels were measured. Women over age 40 in these different cities were divided into 3 groups according to their age group. Results: A total of 558 woman were included in the study. Vitamin D levels in the 3 cities were found to be significantly different from each other (p<0.05). In Istanbul in both group 1 (40-49 years) and 2 (50-59 years) a weakly significant correlation was found between Vitamin D level and L1-4 T-score (r= -0.50, p<0.01) as well as serum calcium level and L1-4 T-score (r= -0.45, p<0.01) (r= -0.46, p<0.01). The significance for the correlation of femoral neck T-score and Vitamin D and calcium levels was weak (r= -0.26, p<0.05 and r=-0.30, p<0.05, respectively). No significant correlation between Vitamin D or calcium levels and T-scores at spinal or femoral neck and total hip T-scores existed for group 3 in Istanbul or any group in Izmir and Osmaniye. Vitamin D levels in Izmir was significantly higher than in Istanbul and Osmaniye. It can be concluded that in Istanbul in 3 groups there was a weakly significant correlation between Vitamin D level and L1-4 T-score (r= -0.44, p<0.001). Conclusion: In this study the most important result was correlation between BMD and low vitamin D levels. We concluded that correlation between BMD and vitamin D levels should be investigated in larger populations. (From the World of Osteoporosis 2010;16:49-52)